Pengelolaan Sampah di Kabupaten Bogor: Tantangan dan Solusi - Muhammad Baharuddin Zubakhrum Tjenreng; Nanang Suryana; Pratiwi Nurhascaryani (Post Graduate School of Government Science, 2025)
Waste management has become one of the most pressing environmental challenges in Indonesia, including in Bogor Regency. The rapid population growth and urban development in the region have significantly contributed to the increasing volume of waste generated from both household and industrial sectors, negatively impacting public health, environmental cleanliness, and overall quality of life. This study aims to identify the key issues surrounding waste management in Bogor Regency and propose sustainable solutions to address them. Using statistical data analysis and a comprehensive literature review, the study reveals two major contributing factors: the inadequacy of waste management infrastructure and the low level of public awareness and participation. These challenges have hindered the effectiveness of existing waste management programs, resulting in persistent problems such as illegal dumping, limited recycling efforts, and the overcapacity of final disposal sites. The findings underscore the urgent need for integrated and community-based waste management strategies that include capacity building, infrastructure development, and behavioral change campaigns. In addition, policy reinforcement and multi-stakeholder collaboration involving local government, the private sector, and civil society are essential to ensuring the long-term success of sustainable waste management initiatives. This research contributes to the growing body of knowledge on environmental governance and provides a practical reference for improving waste management practices in rapidly developing regions.